2017
DOI: 10.1002/hbm.23899
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ventral tegmental area input on cortico‐subcortical networks underlying action control and decision making

Abstract: It is argued that the mesolimbic system has a more general function in processing all salient events, including and extending beyond rewards. Saliency was defined as an event that is unexpected due to its frequency of occurrence and elicits an attentional-behavioral switch. Using functional magnetic resonance imaging (fMRI), signals were measured in response to the modulation of salience of rewarding and nonrewarding events during a reward-based decision making task, the so called desire-reason dilemma paradig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
(56 reference statements)
1
7
0
Order By: Relevance
“…Contrary to previous observations investigating reward processing as a function of reward sensitivity, where the mesolimbic and mesocortical pathways are relevant (Costumero et al, 2013a;Costumero et al, 2013b; for a review see Kennis, Rademaker, & Geuze, 2013), the absence of emotional stimuli seems to move the focus of attention to the mesocortical pathway. The results of a recent study are consistent with this pattern (Richter & Gruber, 2018). This study compared the brain areas involved in processing salient infrequent stimuli to those involved in processing salient rewarding stimuli.…”
Section: Discussionsupporting
confidence: 74%
“…Contrary to previous observations investigating reward processing as a function of reward sensitivity, where the mesolimbic and mesocortical pathways are relevant (Costumero et al, 2013a;Costumero et al, 2013b; for a review see Kennis, Rademaker, & Geuze, 2013), the absence of emotional stimuli seems to move the focus of attention to the mesocortical pathway. The results of a recent study are consistent with this pattern (Richter & Gruber, 2018). This study compared the brain areas involved in processing salient infrequent stimuli to those involved in processing salient rewarding stimuli.…”
Section: Discussionsupporting
confidence: 74%
“…Against this background, we speculate that in DM1 patients a VTA-mediated dopaminergic overflow may produce a hyperconnectivity in BA6 and BA4, thus reducing patients' ability to anticipate the reward/punishment and learn a winning strategy. Consistent with this hypothesis, it has been previously shown that VTA dopaminergic neurons respond to the reward system (Schultz, Dayan, Montague, 1997;Brocka, et al, 2018) and play a critical role in adaptive decision-making (Richter & Gruber, 2018). Additionally, a dopaminergic overdose induced by replacement therapy was demonstrated to affect decision-making in patients with Parkinson's disease (Evans, Hoefler, Biber & Lueken, 2016).…”
Section: Discussionmentioning
confidence: 77%
“…Among these, there is the ventral tegmental area (VTA), a brainstem structure, which is particularly rich in dopaminergic neurons that project diffusely to several subcortical and cortical areas, including the prefrontal cortex (Schultz, Dayan & Montague, 1997). This complex system is mainly implicated in reward mechanisms as shown in previous animal (Schultz, Dayan & Montague, 1997) and human studies (Krebs, Heipertz, Schuetze & Duzel, 2011;Richter & Gruber, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Populated mainly with dopaminergic (DA) neurons, the VTA plays important roles in reward, motivation and attention (Schultz, 1998; Schultz & Dickinson, 2000). The role of SC-VTA pathway might be modulating the level of arousal (Eban-Rothschild et al, 2016) or changing the attentional state (Redgrave et al, 1999; Richter & Gruber, 2018) of the observer to mediate rapid defensive responses (Becerra et al, 2001).…”
Section: Discussionmentioning
confidence: 99%